2011
DOI: 10.1530/rep-10-0332
|View full text |Cite
|
Sign up to set email alerts
|

Heifer nutrient intake during early- and mid-gestation programs adult offspring adiposity and mRNA expression of growth-related genes in adipose depots

Abstract: Changes in maternal nutrient intake during gestation alter IGF receptor abundance and leptin (LEP) mRNA expression in fetal adipose tissue. It is not known whether such changes persist into adult life and whether they are associated with an effect on phenotype. We investigated the effect of high (240%) and low (70%) levels of recommended daily crude protein intake for beef heifers during the first and second trimesters of gestation on singleton progeny (nZ68): subcutaneous (SC) adipose tissue depth at rump (P8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…Martin et al (2007) further reported no influence of maternal protein supplementation on age at puberty of the daughters. Combined with a lack of difference in the number of antral follicles detectable by ultrasonography at 14 months of age in the present study, this could indicate that the increased proportion of heifers calving in the first 21 d is due to changes in adiposity (Micke et al, 2011) or altered uterine function. Clearly, the increased proportion of heifers calving in the first 21 d was not due to greater rates of growth, decreased age at puberty, or a greater number of antral follicles.…”
Section: Traitmentioning
confidence: 49%
“…Martin et al (2007) further reported no influence of maternal protein supplementation on age at puberty of the daughters. Combined with a lack of difference in the number of antral follicles detectable by ultrasonography at 14 months of age in the present study, this could indicate that the increased proportion of heifers calving in the first 21 d is due to changes in adiposity (Micke et al, 2011) or altered uterine function. Clearly, the increased proportion of heifers calving in the first 21 d was not due to greater rates of growth, decreased age at puberty, or a greater number of antral follicles.…”
Section: Traitmentioning
confidence: 49%
“…However, there could have been changes in expression of growth factors that had already occurred that caused the differences in adipocyte size or nimibers because we observed no increase in overall fat mass in this experiment. Adipose tissues from offspring from protein-restricted mothers have altered expression of components of the IGF system (Micke et al, 2011). This could have resulted in altered adipose tissue growth.…”
Section: Discussionmentioning
confidence: 99%
“…Sex-specific differences in adipose gene expression emerge by late gestation and dominate in early postnatal life, reflecting the significantly greater adiposity in females versus males (Wallace et al 2014b. Sex-specific differences in adipose gene expression in different fat depots have also been reported in adult cattle (Micke et al 2011b) following early gestational maternal dietary perturbation.…”
Section: Evidence For Programming Of Body Fatmentioning
confidence: 97%
“…There is also one cattle study (Long et al 2010a) suggesting that overnutrition throughout gestation results in increased adiposity in older offspring (at 22 vs 19 months). Cattle studies by Micke et al (2010aMicke et al ( , 2011aMicke et al ( , 2011b show that the maternal diet during the first and second trimesters alters growth and carcass development, including fat deposition, from weaning through to slaughter at 22 months of age in a sex-specific manner. One of the main problems in trying to draw conclusions from these various studies is the variability in the timing of the nutritional insult and the age at which the offspring are studied.…”
Section: Body Fat or Adipositymentioning
confidence: 99%